Integrativeness in Malaysia: The socio-educational model in a modern Asian context. (December 2021) - Rock, David; Danaee, Mahmoud; Coluzzi, Paolo
Abstract: The continuing impact of Gardner's notion of integrativeness on the field of second language motivation (SLM) was recently highlighted in a prominent edited volume, the publication and contents of which imply that, even today, the notion should not be sidelined. However, important theoretical criticisms of integrativeness, such as the claim that since English is now a lingua franca it is no longer associated with a specific speaker community, have been raised. This study discusses several prominent criticisms of integrativeness, investigates the degree to which attitudes indicating integrativeness are present in a cohort of modern Malaysian high school students learning English, seeks to account for such findings in the modern Malaysian context, and explores the implications of the findings for the status and potential utility of integrativeness and the socio-educational model. An adapted questionnaire was used to collect attitudinal data from 278 upper secondary students in the Klang Valley, Malaysia, and the results were statistically analyzed. Moderately high levels of integrativeness were found among the participants. This finding implies that integrativeness and the socio-educational model may have continuing relevance in the modern world.